Perceptions on the utilisation of sanitation for rural agricultural food security production in Ga-Mothapo Community in Polokwane Local Municipality, Limpopo - Maponya, Maphohla Ennie (My University, 2016)
In South Africa, particularly in the Limpopo Province, the handling of human excreta and the use of human excreta for food production are still not valued and generally not acceptable. The issue of social acceptance is one of the several issues that must be tackled in order to successfully institute the practice of human waste reuse in agriculture. As such, this study explored the attitudes and perceptions towards the utilisation of urine and faeces as the alternative to chemical fertilizer in a rural agriculture in Ga-Mothapo, Polokwane Local Municipality in Limpopo. The study adopted a qualitative approach using a case study design. Data was collected using face to face interviews. A majority of the households indicated that they are not comfortable with the idea of using human excreta for agricultural purpose. According to them, it was against their cultural beliefs and it is a taboo to use the waste of human as they prefer to use animal waste instead. The health risk and environmental contamination were also highlighted by the households as weighing against the use of human excreta. Even though some respondents mentioned that using human excreta has the potential to enrich their depleted agricultural soils, and that it had the effect of reducing the cost of buying commercial fertilizers, they still felt uncomfortable using it. This study concludes by recommending that there is a need for constant intervention and awareness to address the issue of food security through ecological sanitation which will promote sustainable agriculture by providing soil with nutrients. Keywords: Ecological Sanitation, Human Excreta, Perceptions, Attitudes, Food Security
Thesis (M. Dev.) -- University of Limpopo, 2016.
Keywords: Ecological Sanitation; Human excreta; Food security; Sanitation -- South Africa; Sanitation, Rural; Food security; Feces; Urine; Toilets